(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The descriptive approach was used in a survey method to solve the research problem. The research community was identified from the third and fourth stage students in the College of Physical Education and Sports Sciences at the University of Basra for the academic year (2022-2021).